The stolen narrative of the Bulgarian Jews and the Holocaust - Comforty, Jacky 1954- (Lexington studies in Jewish literature, 2021)
"This book collects narratives of Bulgarian Jews who survived the Holocaust. Through eye-witness testimonies, archival documents, photographs, and researchers' investigations, the stories counter official accounts and corroborate war crimes."